A Journey From SARS-CoV-2 to COVID-19 and Beyond: A Comprehensive Insight of Epidemiology, Diagnosis, Pathogenesis, and Overview of the Progress into Its Therapeutic Management - Shoaib, Muhammad Harris; Ahmed, Farrukh Rafiq; Sikandar, Muhammad; Yousuf, Rabia Ismail; Saleem, Muhammad Talha (Frontiers in Pharmacology, 2021)
The 2019 novel coronavirus (2019-nCoV), commonly known as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) or coronavirus disease 2019 (COVID-19), was first revealed in late 2019 in Wuhan city, Hubei province, China that subsequently spread globally thereby declared as a pandemic by WHO in March 2020. The disease causes severe acute respiratory illness and is highly contagious due to the fast-onward transmission. As of the mid of November 2020, the disease has affected 220 countries with more than 16 million active cases and 1.3 million deaths worldwide. Males, pregnant women, aged, immunosuppressed, and those with underlying medical conditions are more vulnerable to the disease than the general healthy population. Unfortunately, no definite treatment is available, and although remdesivir as an antiviral had been approved for use in above 12 years of age and 40 kilograms weight group, it has been observed ineffective is large scale SOLIDARITY trails by WHO. Moreover, dexamethasone has been found to increase the recovery rate of ventilated patients, oxygen, inhaled nitric oxide as a vasodilator has been given emergency expanded access. In addition, more than 57 clinical trials are being conducted for the development of the vaccines on various platforms. Two vaccines have already announced significantly promising phase III results. It is concluded that till the approval of a specific treatment or development of a vaccine against this deadly disease, the preventive measures should be followed strictly to reduce the spread of the disease.